A wet film and its preparation method and application

CN122941033APending Publication Date: 2026-10-20QINGDAO ZHONGKEHUALIAN ADVANCED MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510447957.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-10
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0002]锂电池在使用过程中会发热,在高温条件下,隔膜可能发生氧化反应,导致其结构受损

Benefits of technology

[0026]与现有技术相比,本发明在湿法聚合物薄膜制备过程中,配置特定熔程抗氧剂和二卤甲烷组成的耐老化剂,通过在萃取工段之后和二次拉伸之前将其涂覆在薄膜上,能够有效提高薄膜抗氧化能力,经过二次拉伸形成的薄膜制品具有耐高温、耐老化性能,同时具有纵横向力学强度均匀、孔径分布均一等特性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005353153230000081
    Figure BDA0005353153230000081
  • Figure BDA0005353153230000091
    Figure BDA0005353153230000091
  • Figure HDA0005353153240000011
    Figure HDA0005353153240000011
Patent Text Reader

Abstract

This invention provides a wet-process thin film, its preparation method, and its application, belonging to the field of thin film preparation technology. The preparation method involves: diluting a polymer base material and mixing it with additives to prepare a cast sheet; then stretching, extracting, coating with an anti-aging agent, and performing a second stretching on the cast sheet to obtain the final product. This invention improves the antioxidant capacity of the thin film by configuring a specific anti-aging agent and coating it onto the film during the wet-process polymer thin film preparation process. The resulting thin film product exhibits high-temperature resistance, aging resistance, uniform longitudinal and transverse mechanical strength, and uniform pore size distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thin film preparation technology, and in particular to a wet-process thin film, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries generate heat during use. Under high temperatures, the separator may undergo oxidation, leading to structural damage. This manifests as a decrease in the separator's mechanical properties, such as reduced tensile strength and thermal stability. Furthermore, high temperatures can cause the separator's pore size to increase, affecting the battery's ion permeability. At high temperatures, the separator's permeability typically increases, meaning its sealing performance decreases, potentially increasing the risk of internal short circuits within the battery.

[0003] Existing wet-process polypropylene lithium battery separators generally have a thickness of 3.5-30μm, tensile strength ≥150MPa, puncture strength ≥450gf, and rupture temperature ≥170℃. They possess advantages such as bidirectional high strength, uniform pore size, high specific resistivity, and high temperature resistance. However, during long-term use, their aging resistance is poor, specifically their resistance to ultra-long-term high-temperature aging. After prolonged aging, the separator becomes brittle and cannot meet the higher requirements of baking processes in lithium battery production. During battery temperature runaway, the internal temperature of the cell will rise rapidly, leading to safety issues. For positive and negative electrodes with relatively high energy density and high activity, their safety cannot be guaranteed, preventing their application in higher-end fields.

[0004] Therefore, it is necessary to develop a lithium-ion battery separator that combines aging resistance, high temperature resistance, excellent mechanical properties, and small and uniform pore size to solve the above-mentioned technical problems.

[0005] In view of the above, this application is hereby submitted. Summary of the Invention

[0006] The purpose of this invention is to provide a wet-process thin film, its preparation method, and its application. By configuring a specific anti-aging agent and coating it on the film during the wet-process polymer film preparation process, the antioxidant capacity of the film is improved. After secondary stretching, a film product is formed. The product has high temperature resistance and aging resistance, and also has the characteristics of uniform longitudinal and transverse mechanical strength and uniform pore size distribution.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] In a first aspect, the present invention provides a method for preparing a wet-process thin film, comprising at least:

[0009] The polymer base material is diluted and mixed with additives to prepare cast sheets;

[0010] The casting is then stretched, extracted, coated with an anti-aging agent, and stretched a second time to obtain the final product.

[0011] Furthermore, the polymer main material includes polypropylene and / or polyethylene, preferably polypropylene.

[0012] Furthermore, the adjuvants include, but are not limited to, nucleating agents and / or antioxidants.

[0013] Optionally, the nucleating agent includes one or more of adipic acid, calcium stearate, aluminum stearate, sorbitol benzylidene derivative, sodium benzoate or bis(p-tert-butylbenzoic acid)carboxyaluminum, aromatic amide or rare earth complex.

[0014] Optionally, the antioxidant includes one or more of antioxidants 1010, 168, 420, 608, 1412, 202, 622, 5050, 501, 228, 9228, 3114, 330, or CA.

[0015] Further, according to the mass fractions, the polymer main material, nucleating agent and antioxidant are 20-60 parts, 0.1-5 parts and 0.01-1 parts, respectively; preferably, the polymer main material, nucleating agent and antioxidant are 25-40 parts, 0.2-3 parts and 0.01-0.5 parts, respectively.

[0016] Furthermore, the diluent used for dilution can be an organic solvent such as white oil, and according to the above-mentioned weight parts calculation rules, it can be 30-80 parts, preferably 50-70 parts. In some other embodiments, a solubilizer can be added.

[0017] The anti-aging agent coating is located between extraction and secondary stretching in the process flow, that is, the coating device is set downstream of the extraction tank and upstream of the secondary stretching equipment; optionally, the coating device includes one or more combinations of roller coating device, spraying device, dot coating device, scraping device, gravure coating device, wire rod coating device, slot coating device, extrusion coating device or dip coating device.

[0018] Further, the anti-aging agent includes a solution of an antioxidant with a melting range of 80-120°C; preferably, the anti-aging agent includes a mixed solution of an antioxidant with a melting range of 80-120°C and an antioxidant with a melting range of 120-125°C.

[0019] Furthermore, the mass ratio of the antioxidant with a melting range of 80-120℃ to the antioxidant with a melting range of 120-125℃ is (8-10):1.

[0020] Preferably, the solvent of the solution or mixed solution is dihalomethane, and the temperature of the subsequent secondary stretching process is around 150°C. At this temperature, the dihalomethane will evaporate, leaving the antioxidant in the pores of the film and preventing the introduction of other new impurities.

[0021] Furthermore, the mass concentration of the solution or mixed solution is 0.01-1%.

[0022] Furthermore, the film coated with the anti-aging agent has a transport speed of 20-200 m / min, and the coating environment temperature can be room temperature. After coating, the anti-aging agent is applied to the surface of the diaphragm. After a second stretching, the antioxidant component in the anti-aging agent dissolves, and the liquid antioxidant is evenly injected into the pores of the film, thereby achieving the anti-aging effect.

[0023] Preferably, the film is dried after extraction and before the anti-aging agent is applied.

[0024] Secondly, the present invention also provides a lithium-ion battery, using a wet-process thin film prepared by the aforementioned method as a separator.

[0025] The membrane has a thickness of 5-30 μm, a porosity of 30-80%, a pore size of 20-200 nm, a biaxial tensile strength ≥100 MPa, an air permeability ≤300 s / 100 cc, a membrane rupture temperature ≥170℃, an aging time of ≥24 h at 160℃, and an aging time of ≥12 h at 170℃.

[0026] Compared with the prior art, the present invention configures an anti-aging agent composed of a specific melting range antioxidant and dihalomethane during the wet polymer film preparation process. By coating the film after the extraction stage and before the secondary stretching, the antioxidant capacity of the film can be effectively improved. The film product formed after the secondary stretching has high temperature resistance and aging resistance, and also has the characteristics of uniform longitudinal and transverse mechanical strength and uniform pore size distribution. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 These are photographs of the thin film prepared in Example 1 of the present invention after thermal aging at 160°C for 24 hours and at 170°C for 12 hours.

[0029] Figure 2 The images show the thin film prepared for Comparative Example 1 of this invention after thermal aging at 160°C for 24 hours and at 170°C for 12 hours. Detailed Implementation

[0030] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0031] As used in this article:

[0032] "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.

[0033] The conjunction "composed of..." excludes any unspecified elements, steps, or components. If used in a claim, this phrase makes the claim closed, excluding materials other than those described, except for associated conventional impurities. When the phrase "composed of..." appears in a clause of the body of a claim rather than immediately following it, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0034] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0035] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.

[0036] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0037] The thickness, tensile strength, puncture strength, areal density, air permeability, thermal shrinkage rate, and thermal aging at 160°C and 170°C of the films prepared in the following examples and comparative examples were measured or characterized, and the results are shown in Table 1.

[0038] Example 1

[0039] A method for preparing a polymer film includes the following steps:

[0040] 3700g of polypropylene with a melt index of 0.5g / 10min and 6300g of 100# white oil were fed into a twin-screw extruder via a powder weigher and a plunger pump. 50g of nucleating agent calcium stearate, 1.5g of antioxidant 1010, 0.75g of antioxidant 228, and 0.75g of antioxidant 420 were added, and the mixture was melt-plasticized at 185℃. The melt was extruded from the die to form a sheet. The gel-like sheet was immediately passed through a pre-set gap between the shaping roller and the guide roller of a casting machine (the surface temperature of the shaping roller and the guide roller was set to 25℃). A cooling tank (cooling medium: water) was added to force-cool the reverse side of the melt at 25℃, forming a 1mm thick cast sheet. This cast sheet was then stretched 9 times along the mechanical direction (MD) at 130℃ using a longitudinal stretching machine, and then stretched 9 times along the width direction (TD) at 140℃ using a transverse stretching machine. The stretched oil film was then passed through an extraction tank containing dichloromethane to extract the white oil from the film, which was then dried. Next, it passed through an anti-aging agent dip-coating system, where an antioxidant was uniformly coated onto the diaphragm surface. The dip-coating process was carried out at room temperature. The anti-aging agent was antioxidant 202 dissolved in dichloromethane at a mass concentration of 0.1%. Antioxidant 202 is a phosphite antioxidant with a melting range between 80℃ and 120℃. The film transport speed during dip-coating was 80 m / min. The resulting film coated with the anti-aging agent entered a transverse stretching machine and was stretched 1.3 times along the TD direction at 150℃, then retracted to 1.1 times along the TD direction, while simultaneously heat-setting at 150℃. Finally, it was wound up using a take-up roller to obtain a film with a thickness of 9.0 μm. Photos of the film after heat aging at 160℃ for 24 hours and at 170℃ for 12 hours are shown below. Figure 1 As shown in the figure, the results of the remaining performance tests are shown in Table 1.

[0041] Example 2

[0042] A method for preparing a polymer film includes the following steps:

[0043] 4000g of polypropylene with a melt index of 2g / 10min and 6000g of 100# white oil were fed into a twin-screw extruder via a powder weigher and a plunger pump. 55.5g of nucleating agent adipic acid, 1.8g of antioxidant 1010, 0.9g of antioxidant 228, and 0.6g of antioxidant 420 were added, and the mixture was melt-plasticized at 185℃. The melt was extruded from the die to form a sheet. The gel-like sheet was immediately passed through a pre-set gap between the shaping roller and the guide roller of a casting machine (the surface temperature of the shaping roller and the guide roller was set to 25℃). A cooling tank (cooling medium: water) was added to force-cool the reverse side of the melt at 25℃, forming a 1.05mm thick cast sheet. This cast sheet was then stretched 9 times along the mechanical direction (MD) at 130℃ using a longitudinal stretching machine, and then stretched 9 times along the width direction (TD) at 140℃ using a transverse stretching machine. The stretched oil film was then passed through an extraction tank containing dichloromethane to extract the white oil from the film, which was then dried. Next, it passed through an anti-aging agent dip-coating system, where an antioxidant was uniformly coated onto the diaphragm surface. The dip-coating process was carried out at room temperature. The anti-aging agent was antioxidant 202 dissolved in dichloromethane at a mass concentration of 0.05%. Antioxidant 202 is a phosphite antioxidant with a melting range between 80℃ and 120℃. The film transport speed during dip-coating was 100 m / min. The resulting anti-aging agent-coated film entered a transverse stretching machine and was stretched 1.3 times along the TD direction at 150℃, then retracted to 1.1 times along the TD direction, while simultaneously heat-setting at 150℃. Finally, it was wound up using a take-up roller to obtain a film with a thickness of 9.1 μm. The performance test results are shown in Table 1.

[0044] Example 3

[0045] A method for preparing a polymer film includes the following steps:

[0046] 4500g of polypropylene with a melt index of 2g / 10min and 7000g of 100# white oil were fed into a twin-screw extruder via a powder scale and a plunger pump. 100g of nucleating agent adipic acid, 1.2g of antioxidant 1010, 1.2g of antioxidant 228, and 1.2g of antioxidant 420 were added, and the mixture was melt-plasticized at 185℃. The melt was extruded from the die to form a sheet. The gel-like sheet was immediately passed through a pre-set gap between the shaping roller and the guide roller of a casting machine (the surface temperature of the shaping roller and the guide roller was set to 25℃). A cooling tank (cooling medium: water) was added to force-cool the reverse side of the melt at 25℃, forming a casting sheet with a thickness of 1.03mm. This casting sheet was then stretched 9 times along the mechanical direction (MD) at 130℃ using a longitudinal stretching machine, and then stretched 9 times along the width direction (TD) at 140℃ using a transverse stretching machine. The stretched oil film was then passed through an extraction tank containing dichloromethane to extract the white oil from the film, which was then dried. Next, it passed through an anti-aging agent dip-coating system, where an antioxidant was uniformly coated onto the diaphragm surface. The dip-coating process was carried out at room temperature. The anti-aging agent was antioxidant 202 dissolved in dichloromethane at a mass concentration of 0.02%. Antioxidant 202 is a phosphite antioxidant with a melting range between 80℃ and 120℃. The film transport speed during dip-coating was 120 m / min. The resulting film coated with the anti-aging agent entered a transverse stretching machine and was stretched 1.3 times along the TD direction at 150℃, then retracted to 1.1 times along the TD direction, while simultaneously heat-setting at 150℃. Finally, it was wound up using a take-up roller, resulting in a film thickness of 9.0 mm. The performance test results are shown in Table 1.

[0047] Example 4

[0048] The difference from Example 1 is that the anti-aging agent includes antioxidant 202 and antioxidant 1010 in a mass ratio of 9:1. The mass concentration of antioxidant 202 is still 0.1% when dissolved in dichloromethane. Antioxidant 202 is a phosphite antioxidant with a melting range of 80℃-120℃. Antioxidant 1010 is a phenolic antioxidant with a melting range of 120℃-125℃. The film thickness is 9.0 mm. The performance test results are shown in Table 1.

[0049] Example 5

[0050] The difference from Example 1 is that the anti-aging agent includes antioxidant 202 and antioxidant 1010 in a mass ratio of 8:1. The mass concentration of antioxidant 202 is still 0.1% when dissolved in dichloromethane. Antioxidant 202 is a phosphite antioxidant with a melting range of 80℃-120℃. Antioxidant 1010 is a phenolic antioxidant with a melting range of 120℃-125℃. The film thickness is 9.0 mm. The performance test results are shown in Table 1.

[0051] Example 6

[0052] The difference from Example 1 is that the anti-aging agent includes antioxidant 202 and antioxidant 1010 in a mass ratio of 10:1. The mass concentration of antioxidant 202 dissolved in dichloromethane is still 0.1%. Antioxidant 202 is a phosphite antioxidant with a melting range of 80℃-120℃. Antioxidant 1010 is a phenolic antioxidant with a melting range of 120℃-125℃. The film thickness is 9.0 mm. The performance test results are shown in Table 1.

[0053] Comparative Example 1

[0054] The difference from Example 1 is that after extraction and drying, the film directly enters the secondary stretching stage without aging agent dipping. The film thickness is 9.0 mm. Photos of the film after heat aging at 160°C for 24 hours and at 170°C for 12 hours are shown below. Figure 2 As shown in the figure, the results of the remaining performance tests are shown in Table 1.

[0055] The thickness, tensile strength, puncture strength, areal density, air permeability, thermal shrinkage rate, and thermal aging of the prepared film were measured, and the results are shown in Table 1.

[0056] Table 1. Test results of the examples and comparative examples.

[0057]

[0058]

[0059] As shown in Table 1, compared with Comparative Example 1, in Examples 1-3, coating with an anti-aging agent after the extraction stage effectively improves the high-temperature aging performance of the film. Comparative Example 1, which only added antioxidants during the raw material blending process to prepare the cast film, could not address the high-temperature aging problem. After dip coating, the membrane surface uniformly adsorbs the mixture of dichloromethane and antioxidant. Following the high-temperature stretching process, the dichloromethane evaporates and is removed, while the antioxidant melts and enters the pores inside the membrane. Antioxidant 202 effectively decomposes the hydrogen peroxide produced during the oxidation reaction in the high-temperature stretching process, preventing the polymer oxidation reaction from continuing.

[0060] As can be seen from Examples 4-6, using antioxidants with two different melting ranges (80℃-120℃ and 120℃-125℃) as anti-aging agents can further improve the high-temperature resistance of the film while maintaining the anti-aging performance of Example 1. Furthermore, with the increase in the proportion of antioxidant 1010, both strength and heat shrinkage properties are improved. The hydrogen atoms in the antioxidant 1010 molecule combine with peroxide free radicals and alkyl free radicals, effectively cooperating with antioxidant 202 to terminate the oxidation reaction.

[0061] pass Figure 1 and Figure 2The comparison shows that the diaphragm of the present invention can still basically maintain its properties after heat aging at 160℃@24h and 170℃@12h, while the diaphragm without anti-aging agent coating is basically damaged after heat aging at 160℃@24h and 170℃@12h.

[0062] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0063] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a wet-process thin film, characterized in that, At least including: The polymer base material is diluted and mixed with additives to prepare castings; The casting is then stretched, extracted, coated with an anti-aging agent, and stretched a second time to obtain the final product.

2. The preparation method according to claim 1, characterized in that, The polymer material includes polypropylene and / or polyethylene; And / or, the adjuvants include nucleating agents and / or antioxidants.

3. The preparation method according to claim 2, characterized in that, The nucleating agent includes one or more of the following: adipic acid, calcium stearate, aluminum stearate, sorbitol benzyl derivative, sodium benzoate, bis(p-tert-butylbenzoic acid)carboxyaluminum, aromatic amide, or rare earth complex. And / or, the antioxidant includes one or more of antioxidant 1010, antioxidant 168, antioxidant 420, antioxidant 608, antioxidant 1412, antioxidant 202, antioxidant 622, antioxidant 5050, antioxidant 501, antioxidant 228, antioxidant 9228, antioxidant 3114, antioxidant 330, or antioxidant CA.

4. The preparation method according to claim 2 or 3, characterized in that, According to the mass fractions, the polymer main material, nucleating agent and antioxidant are 20-60 parts, 0.1-5 parts and 0.01-1 parts, respectively.

5. The preparation method according to claim 1, characterized in that, The anti-aging agent includes a solution of an antioxidant with a melting range of 80-120°C.

6. The preparation method according to claim 5, characterized in that, The anti-aging agent includes a mixed solution of an antioxidant with a melting range of 80-120℃ and an antioxidant with a melting range of 120-125℃. The mass ratio of the antioxidant with a melting range of 80-120℃ to the antioxidant with a melting range of 120-125℃ is (8-10):

1.

7. The preparation method according to claim 5 or 6, characterized in that, The solvent for the solution or mixed solution is dihalomethane.

8. The preparation method according to claim 7, characterized in that, The mass concentration of the solution or mixed solution is 0.01-1%.

9. The preparation method according to claim 1, characterized in that, The film is dried after extraction and before the anti-aging agent is applied.

10. A lithium-ion battery, characterized in that, The wet-process film prepared by any one of claims 1-9 is used as the separator.